KAJIAN LITERATUR : PENGARUH WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN MAKANAN KERIPIK BALADO DI SUMATERA BARAT - Qumil Laila Arham; Sri Nova Deltu; Rahmad Saputra; Relifra Relifra (J-MIND (Jurnal Manajemen Indonesia), 2023)
The purpose of this research is to find out how the influence of word of mouth on the purchasing decision of balado chips in West Sumatra. This study uses a literature review analysis with sources such as Sciencedirect, Researchgate, and Google Scholar. There are ten articles analyzed. Literature studies were also conducted on various book sources and internet sources. The results showed that word of mouth had a positive impact on purchasing decisions for balado chips. Balado chips also have their own characteristics and characteristics. The results of this literature review research indicate that purchasing decisions on Balado chips can be increased by positive word of mouth and improved marketing strategies to create future purchases.